The creation of enterprises and strategy. Reflections from the resource perspective (2011)
The two most important administrative disciplines in the last decades are the creation of enterprises and strategy. The interest for them has been not on pragmatic but also academic. It is also a product of the need the enterprises have of guarantee their permanence in the market, and the necessity of economics of promoting their adequate development and growth. The strategy arises as a support of enterprise decisions with regard to their growth and consolidation, and of enterprise creation as a revitalizing element and a welfare generator one. This theoretical article deals with one of the academic discussions, which has aroused greater interest in the field of management: the relation enterprise creation- strategy. We aim to analyze such relation starting from the strategic approach of capabilities and resources, with the objective of stating clearly potential contact links between enterprise creation and strategy, in order to contribute to a greater knowledge and use the two disciplines.